Effect of Faecalibacterium prausnitzii on intestinal barrier function and immune homeostasis : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science, Massey University, Manawatū, New Zealand - Maier, Eva (Massey University, 2017)
Various gastrointestinal (GI) diseases, for example inflammatory bowel disease, are linked to impaired barrier function, chronic inflammation and dysbiosis of the resident microbiota. Faecalibacterium prausnitzii, an abundant obligate anaerobe of the healthy human microbiota, has reduced abundance in the GI tract of people with these diseases, and has been suggested to exert beneficial effects. Only a few studies have investigated its mechanisms of action, partly due to the difficulty of co-culturing live obligate anaerobes with oxygen-requiring human cells. The novel apical anaerobic co-culture model used in this study allows this co-culture through the separation of anaerobic and aerobic compartments. This model was used to investigate the effects of live F. prausnitzii (strains A2-165, ATCC 27768 and HTF-F) on intestinal barrier integrity, measured by transepithelial electrical resistance (TEER) of the intestinal epithelial cell line Caco-2, and on immune homeostasis, specifically on Toll-like receptor (TLR) activation. Method development was required to adapt these assays to the novel model and to optimise the growth of F. prausnitzii co-cultured with Caco-2 cells and TLR-expressing cell lines while maintaining their viabilities. Firstly, the optimised co-culture conditions were used to determine the effect of the three F. prausnitzii strains on barrier integrity of healthy and tumour necrosis factor alpha (TNF-α) treated Caco-2 cells. Live and growing F. prausnitzii did not alter the TEER across healthy Caco-2 cells. However, under TNF-α mediated inflammatory conditions, dead F. prausnitzii decreased TEER, whereas live bacteria maintained TEER. Secondly, the TLR activation assay was adapted to be carried out in the novel model. Using the adapted assay conditions it was determined that live F. prausnitzii induced greater TLR2 and TLR2/6 activation than dead F.prausnitzii. Collectively, these results indicate greater immuno-stimulatory effects of live F. prausnitzii, via TLR2 activation, and this effect is potentially linked to its barrier maintaining properties, because previous research showed enhancement of barrier integrity induced by TLR2 signalling. This new knowledge contributes to the understanding of how F. prausnitzii may maintain immune homeostasis in the GI tract. Unravelling the biological mechanisms used by prevalent species of the human microbiota, such as F. prausnitzii, will ultimately allow better comprehension of microbial regulation of GI function.
Keywords: Intestines; Microbiology; Gastrointestinal mucosa; Immune system; Homeostasis; Research Subject Categories::MEDICINE::Microbiology, immunology, infectious diseases